CORRECTION PROCEDURE FOR THE DETERMINATION OF SOIL SPECIFIC SURFACE (Journal of Engineering, 2010)
Specific surface has a very important role in geotacnic especially with that home dell with gypseous soils or other types of salty soils. Because its calculation need for high accuracy, a procedure is presented to calculate a correction factor for Specific surface determination.In a previous work, grain size distribution curves of many soil samples are collected. A value for the specific surface of each soil is determined summing the surface area of subintervals in the distribution curve.In this work, the values of specific surface are obtained from these gradation curves and compared to those calculated using the values of the equivalent diameter for each soil. Fitting has been made and gets the best equation representing these points. From this equation, new values for specific surface are obtained by interning the specific surface calculated from the equivalent diameter and again the point is draw with the origin point (specific surface obtained from these gradation curves). Fitting is made again and the new equation is obtained. Finally, the equation of the calculated corrected specific surface is written. The results showed a very good agreement when using the corrected procedure.